Comparison of E-learning, M-learning and Game-based learning in programming education – A gendered analysis - Malik, Sohail Iqbal; Al-Emran, Mostafa; Mathew, Roy; Tawafak, Ragad Moufaq; Al Farsi, Ghaliya (IJET, 2020)
Learning to code is considered as a difficult and challenging task for a significant number of novice programmers in programming education. Novice programmers have to acquire different skills such as problem solving, program design, comprehension, and debugging at the same time. On the other hand, most introductory programming courses focus more on syntax of the pro-gramming language. In this study, we developed and introduced a ‘PROBSOL’ application in three different learning systems (E-learning, M-learning and Game-based learning) to enhance the problem solving skills of novice pro-grammers in an introductory programming (IP) course. A survey was conducted with the IP students to determine their perception about all the three applica-tions in the IP course. Gender differences were determined by comparing both female and male students’ responses for each question in the survey. The results of comparison show that male students were more satisfied with all the three applications compared to female students. Both female and male students per-ceived that all the three applications are user-friendly, enabled them to accom-plish tasks more quickly, and enhanced their learning productivity. Overall, both male and female students appreciated all the three applications in the teaching and learning process of the IP course.This study implies that instruc-tors can also use all the three applications as an additional teaching tool in the teaching and learning process of programming education.